Role of endocytosis in the internalization of spermidine-C(2)-BODIPY, a highly fluorescent probe of polyamine transport - Soulet, Denis; Covassin, Laurence; Kaouass, Mohammadi; Charest-Gaudreault, Rene; Audette, Marie; Poulin, Richard (Biochemical Journal, 2002)
The mechanism of transmembrane polyamine internalization in mammalian cells remains unknown. A novel fluorescent spermidine conjugate [Spd-C(2)-BODIPY; N-(4,4-difluoro-5,7-dimethyl-4-bora-3a,4a-diaza-s-indacene-3-propionyl)-N' -(S -[spermidine-(N(4)-ethyl)]thioacetyl)ethylenediamine] was synthesized from N(4)-(mercaptoethyl)spermidine by a simple, one-step coupling procedure. In Chinese-hamster ovary (CHO) cells, Spd-C(2)-BODIPY accumulation was inhibited by exogenous putrescine, spermidine and spermine, was subject to feedback transport inhibition and was up-regulated by prior polyamine depletion achieved with a biosynthetic inhibitor. Probe internalization was decreased by about 85% in a polyamine-transport-deficient CHO mutant cell line. Using confocal laser scanning fluorescence microscopy, internalized Spd-C(2)-BODIPY was concentrated in vesicle-like structures similar to the recycling endosomes observed with fluorescent transferrin, which partly co-localized with the polyamine probe. In yeast, Spd-C(2)-BODIPY uptake was stringently dependent on receptor-mediated endocytosis, as determined with a mutant defective in early- endosome formation. On the other hand, Spd-C(2)-BODIPY did not mimic the substrate behaviour of natural polyamines in yeast, as shown by the lack of correlation of its uptake characteristics with the phenotypes of mutants defective in either polyamine transport or biosynthesis. These data suggest that endocytosis might be an integral part of the mechanism of polyamine transport in mammalian cells, and that the mammalian and yeast transport systems use qualitatively different transport mechanisms. However, the current data do not rule out the possibility that sequestration of the probe into vesicular structures might be secondary to its prior uptake via a "classical" plasma membrane carrier. Spd-C(2)-BODIPY, a highly sensitive probe of polyamine transport with biochemical parameters qualitatively similar to those of natural polyamines in mammalian cells, should be very useful for dissecting the pathway responsible for polyamine internalization.
The information about affiliations in this record was updated in December 2015. The record was previously connected to the following departments: Neuronal Survival (013212041)